Analysis of The Main Factor In The Implementation of Open Defecation Free Using The AHP Method - Dwiputri, Vica Asrianti; Dewi, Ova Candra (UI Scholars Hub, 2023)
Environmental sanitation refers to an environment's health status, including housing, sewage disposal, clean water supply, waste management, and other factors. Sustainable Development Goals 6 (SDG 6) ensures people access proper environmental sanitation. Based on the monitoring and evaluation results of Community-Based Total Sanitation (STBM) in 2022, it was found that 100% of open defecation had been stopped for Pillar 1 of STBM. This study aims to identify the factors that influence the success of implementing Open Defecation Free (ODF) programs in Depok City. There are two stages in this study to determine the priority factors that influence the success of the Implementation of Open Defecation Free in Depok City using the AHP method. The first stage is identifying the factor, which is based on previous literature that has been done, as these factors are considered to have a significant influence and role in the success of program implementation. This study's factors were related to the contextual, psychosocial, and technological aspects, and The second stage involves data collection through a questionnaire distributed to 35 respondents who were analyzed using the AHP method. The results of this study are the main influential factors, such as personal background, knowledge of the importance of community sanitation, and ownership/maintenance of physical products, can lead to the effective implementation of ODF programs. However, it is essential to note that the success of ODF programs may vary depending on the specific context in which they are implemented. Thus a tailored approach may be necessary.